HST spectrum and timing of the ultracompact X-ray binary candidate 47 Tuc X9 - Tudor, V.; Miller-Jones, James; Knigge, C.; Maccarone, T.; Tauris, T.; Bahramian, A.; Chomiuk, L.; Heinke, C.; Sivakoff, G.; Strader, J.; Plotkin, R.; Soria, R.; et al. (Oxford University Press, 2018)
To confirm the nature of the donor star in the ultracompact X-ray binary candidate 47 Tuc X9, we obtained optical spectra (3000–10 000 Å) with the Hubble Space Telescope / Space Telescope Imaging Spectrograph. We find no strong emission or absorption features in the spectrum of X9. In particular, we place 3σ upper limits on the H α and He ii λ4686 emission line equivalent widths − EWH α ≲ 14 Å and −EW HeII ≲9 −EWHeII≲9 Å, respectively. This is much lower than seen for typical X-ray binaries at a similar X-ray luminosity (which, for L 2--10keV ≈10 33 --10 34 L2--10keV≈1033--1034 erg s−1 is typically − EWH α ∼ 50 Å). This supports our previous suggestion, by Bahramian et al., of an H-poor donor in X9. We perform timing analysis on archival far-ultraviolet, V- and I-band data to search for periodicities. In the optical bands, we recover the 7-d superorbital period initially discovered in X-rays, but we do not recover the orbital period. In the far-ultraviolet, we find evidence for a 27.2 min period (shorter than the 28.2 min period seen in X-rays). We find that either a neutron star or black hole could explain the observed properties of X9. We also perform binary evolution calculations, showing that the formation of an initial black hole/ He-star binary early in the life of a globular cluster could evolve into a present-day system such as X9 (should the compact object in this system indeed be a black hole) via mass-transfer driven by gravitational wave radiation.